Comparative Investigation of Pollution Accumulation and Natural Cleaning for Different HV Insulators - Dimitropoulou, M.; Pylarinos, D.; Siderakis, K.; Thalassinakis, E.; Danikas, M. (Engineering, Technology & Applied Science Research, 2015)
High Voltage insulators are scattered throughout any HV network and a single insulator fault may cause an excessive outage. Reliability is a key issue for electric power systems and fault-free performance of insulators greatly reflects on the reliability of the system. Environmental influence is rather important for the optimum selection of outdoor insulators and, therefore, field measurements provide valuable information. Utilities perform such measurements in order to decide upon the location/route of new HV installations (substations, lines etc) and also to optimize the selection, maintenance and replacement of already installed insulators. A rather interesting case in Greek territory is the island of Crete, due to the coastal development of the network and the local weather conditions. The Greek utility has employed a variety of remedies to cope with the pollution problem. Following the positive feedback after the installation on certain tower in the past, a large project to replace all ceramic insulators with new polymer ones of hydrophobic surface is now in progress. Polymer coatings have also been extensively applied on substations and also on certain areas/towers of the transmission network in the past. In order to investigate the pollution accumulation and the impact of natural washing on different insulator types, a series of periodical ESDD and NSDD pollution measurements were conducted in HEDNO’s TALOS High Voltage Test Station for a 3-months period. Multiple measurements were performed on each insulator every month in order to collect additional data. Five different insulators were selected based on the types historically used in the Cretan Network. Along with the standard glass disc profile, two strings of glass fog profile (the one coated with RTV) and two long-rod composite insulators of different shed profile and material were used. Results are presented and discussed in this paper.